DASHBOARD BUSINESS INTELLIGENCE SEBAGAI PENUNJANG KEPUTUSAN MENENTUKAN JUMLAH KELAS - Purnamasari, Susan Dian; Kunang, Yesi Novaria (Universitas Bina Darma, 2014)
In the process of academic scheduling courses conducted each semester,components related to the process of scheduling the course coverstime , faculty who teach , classrooms and the number of classes to be opened. determination the number of classes that will be opened by the possible number of students who will taking the course . Obstacles often encountered in scheduling eye Tuition class unbalance between opened and the number of students who take courses. Needabsence of accurate analysis to determine the number of students who will takesubjects based on history data value last semester. Business Intelligenceasa toolaids to process and analyze the data value collected in the data mart , and then perform data analysis by establishingcubes , fact and dimension that can be used as a basis for making applicationbusiness intelligence determination of the number of classes to be opened.